The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1186/s13071-018-2948-8
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium and intestinal parasite perturbations of the infected host’s inflammatory responses: a systematic review

Abstract: Co-infection of malaria and intestinal parasites is widespread in sub-Saharan Africa and causes severe disease especially among the poorest populations. It has been shown that an intestinal parasite (helminth), mixed intestinal helminth or Plasmodium parasite infection in a human induces a wide range of cytokine responses, including anti-inflammatory, pro-inflammatory as well as regulatory cytokines. Although immunological interactions have been suggested to occur during a concurrent infection of helminths and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 148 publications
(101 reference statements)
0
5
0
Order By: Relevance
“…Interactions between the two parasites alter immune responses, thus influencing susceptibility to clinical malaria (92, 93). There are conflicting reports on the outcome of these interactions as some studies have reported enhanced severity (94, 95), others reduced severity (96, 97) yet others have revealed no association between helminth co-infection and malaria outcome (98, 99). These observations may be due to differences in the co-infecting helminth species (100), the host's level of immunity to P. falciparum (101) and differences in study design (91).…”
Section: Immunomodulation In Asymptomatic Malariamentioning
confidence: 99%
“…Interactions between the two parasites alter immune responses, thus influencing susceptibility to clinical malaria (92, 93). There are conflicting reports on the outcome of these interactions as some studies have reported enhanced severity (94, 95), others reduced severity (96, 97) yet others have revealed no association between helminth co-infection and malaria outcome (98, 99). These observations may be due to differences in the co-infecting helminth species (100), the host's level of immunity to P. falciparum (101) and differences in study design (91).…”
Section: Immunomodulation In Asymptomatic Malariamentioning
confidence: 99%
“…However, it is crucial to consider the specific pathogen and the type of immune response elicited, as IL-4 can have both protective and detrimental effects depending on the context. High IL-4 levels have a significant impact on the modulation of effector elements that alter the physiology of the intestine, creating an unfavorable environment for worm parasites [ 108 , 109 ]. The administration of IL-4 from an external source can effectively treat persistent worm infections, whereas the use of IL-4 antagonists hinders the protective responses against such infections [ 110 , 111 ].…”
Section: Anti-inflammatory Cytokinesmentioning
confidence: 99%
“…Studies on concomitant infections in humans suggest that A. lumbricoides infection may protect against cerebral malaria [10,11], while other studies suggest that children infected by Schistosoma mansoni may be more susceptible to P. falciparum infections and develop acute malaria episodes [12,13]. Also, it has been shown that the levels of TNF-α, IL-2, IL-10, IL-6 in Plasmodium-helminth co-infected individuals were significantly higher than the malaria-positive (MP) group [14] dampening the immune response to malaria. However, to our knowledge, no studies have been conducted regarding host immune responses to malaria in children co-infected with protozoan pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…falciparum infections and develop acute malaria episodes [ 12 , 13 ]. Also, it has been shown that the levels of TNF-α, IL-2, IL-10, IL-6 in Plasmodium -helminth co-infected individuals were significantly higher than the malaria-positive (MP) group [ 14 ] dampening the immune response to malaria. However, to our knowledge, no studies have been conducted regarding host immune responses to malaria in children co-infected with protozoan pathogens.…”
Section: Introductionmentioning
confidence: 99%